Fractal dimension of random attractors for non-autonomous fractional stochastic Ginzburg–Landau equations with multiplicative noise. Issue 2 (3rd April 2019) - Lan, Yun; Shu, Ji
ABSTRACT: This paper deals with the asymptotic behaviour of solutions for non-autonomous stochastic fractional Ginzburg–Landau equations driven by multiplicative noise withα ∈ ( 0, 1 ) . We first present some conditions for bounding the fractal dimension of a random invariant set of non-autonomous random dynamical system. Then we derive uniform estimates of solutions and establish the existence and uniqueness of tempered pullback random attractors for the equations inL 2 ( R n ) . At last, we prove the finiteness of fractal dimension of random attractors.